2016
DOI: 10.1186/s13041-016-0227-1
|View full text |Cite
|
Sign up to set email alerts
|

Histamine 1 receptor-Gβγ-cAMP/PKA-CFTR pathway mediates the histamine-induced resetting of the suprachiasmatic circadian clock

Abstract: BackgroundRecent evidence indicates that histamine, acting on histamine 1 receptor (H1R), resets the circadian clock in the mouse suprachiasmatic nucleus (SCN) by increasing intracellular Ca2+ concentration ([Ca2+]i) through the activation of CaV1.3 L-type Ca2+ channels and Ca2+-induced Ca2+ release from ryanodine receptor-mediated internal stores.ResultsIn the current study, we explored the underlying mechanisms with various techniques including Ca2+- and Cl−-imaging and extracellular single-unit recording. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 69 publications
2
15
0
Order By: Relevance
“…It has been demonstrated that H1HR stimulates phospholipase to generate IP and DAG, leading to activation of PKC [16,17]. In addition, H1 receptor activation also stimulates AC to generate cAMP, which in turn activates PKA [20,35]. Mechanistically, our results demonstrated that the activation of PKA but not PKC was involved in H1HRmediated HCC growth and metastasis.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…It has been demonstrated that H1HR stimulates phospholipase to generate IP and DAG, leading to activation of PKC [16,17]. In addition, H1 receptor activation also stimulates AC to generate cAMP, which in turn activates PKA [20,35]. Mechanistically, our results demonstrated that the activation of PKA but not PKC was involved in H1HRmediated HCC growth and metastasis.…”
Section: Discussionsupporting
confidence: 52%
“…It is well established that PKC and PKA signaling is commonly triggered by the activation of histamine receptors [16][17][18][19][20]. To test whether PKC and PKA were activated by H1HR in HCC cells, the activities of PKC and PKA were detected in SNU-368 and HLE cells with H1HR knockdown or overexpression.…”
Section: Activation Of Pka Pathways Is Involved In H1hrmediated Growtmentioning
confidence: 99%
“…7 The marked differences in sleep phase measurements among patients with CF compared with control volunteers without CF (Table 3) support the possibility that CF is associated with circadian rhythm delay, and the lack of significant associations with disease severity markers is consistent with the possibility that sleep phase delay is a novel clinical manifestation of circadian cycle abnormality due to CFTR dysfunction in the CNS. 21 Later sleep onset was associated with longer sleep latency and later wake times in patients with CF, relationships not seen in volunteers without CF (Table 4). All study participants had decreased sleep duration associated with later sleep onset; however, the effect was twice as large in volunteers.…”
Section: Discussionmentioning
confidence: 91%
“…Defective CFTR expression in the brain may lead to detectable abnormalities. [13][14][15] Dysfunctional CFTR protein in the retina 16,17 and anterior hypothalamus [18][19][20] may phase shift and reduce the adaptability of the master circadian clock, 21 adversely affecting health, [22][23][24][25][26][27] social functioning, [28][29][30][31] and quality of life. 22,[32][33][34][35] Because sleep phase delay is commonly associated with circadian phase delay, we performed a pilot study of sleep phase using noninvasive low-cost, but effective, tools.…”
mentioning
confidence: 99%
“…This "circadian gating" is indeed bidirectional in nature. Some targets of the clock include immuneinflammatory responses (16,18,25,44,51), oxidative stress response (15,38), proliferation (37), remodeling (14,48), intracellular calcium concentration ([Ca 2ϩ ] i ) (26,28,33,35,36), and metabolism (23,45): pathways highly relevant to chronic respiratory disease physiology. In the laboratory setting, clock disruption animal models (e.g., BMAL1 knockout; altered light-dark cycles) reveal detrimental effects on lung function (4,12,39,53) and increased susceptibility and inflammatory response to infection with poorer recovery outcomes (16,18,21,32,44,47,48,53).…”
mentioning
confidence: 99%